Long-term care policy in Taiwan: the roles of institutions, political actors, and ideas - Green, Felicia Marie (Nanyang Technological University, 2024)
The development of a long-term care policy is important to ensure that the elderly population is well taken care of and that the assistance or the long-term care services they require are within reach, whether physically or financially. Hence, it is important to understand what influences the formation of long-term care policy. This paper attempts to examine how the roles of institutions, political actors, and ideas contribute to the shaping of the long-term care policy in Taiwan. Through the lens of historical institutionalism, this paper seeks to gain a deeper understanding how the three factors interact with each other and how the interplay of factors shape the long-term care policy in Taiwan. This paper finds that the role of institutions have a more direct influence in constructing the long-term care policy in Taiwan, however, the role of political actors and ideas, are also consequential in the shaping the long-term care policy in Taiwan, hence their role as well as influence should not be undermined.